Shaking off the blow: Plant adjustments during submergence and post-stress growth in Lotus forage species - Buraschi, Florencia Belén (2023)
Flooding significantly hampers global forage production. In flood-prone regions, Lotus tenuis and Lotus corniculatus are common forage legumes, yet little is known about their responses to partial or complete submergence. To address this, we evaluated 10 Lotus accessions subjected to 11 days of either partial or complete submergence, analysing growth traits related to tolerance and recovery after de-submergence. Principal component analyses revealed that submergence associated growth parameters were linked to L. corniculatus accessions, whereas recovery was associated with L. tenuis accessions. Notably, in L. tenuis, recovery from complete submergence positively correlated with leaf mass fraction but negatively with root mass fraction, showing an opposite pattern than in L. corniculatus. Encouragingly, no trade-off was found between inherent growth capacity and submergence tolerance (both partial and complete) or recovery ability, suggesting genetic selection for increased tolerance would not compromise growth potential. L. tenuis exhibited accessions with both partial and complete submergence tolerance, making them versatile for flood-prone environ-ments, whereas L. corniculatus accessions were better suited for partial submergence. These findings offer valuable insights to enhance forage production in flood-prone areas and guide the selection of appropriate Lotus accessions for specific flood conditions.